ART‐RRT: As‐Rigid‐As‐Possible exploration of ligand unbinding pathways - Nguyen, Minh Khoa; Jaillet, Léonard; Redon, Stéphane (Journal of computational chemistry, 2018)
This article proposes a method to efficiently generate approximate ligand unbinding pathways. It combines an efficient tree‐based exploration method with a morphing technique from Computer Graphics for dimensionality reduction. This method is computationally cheap and, unlike many existing approaches, does not require a reaction coordinate to guide the search. It can be used for finding pathways with known or unknown directions beforehand. The approach is evaluated on several benchmarks and the obtained solutions are compared with the results from other state‐of‐the‐art approaches. We show that the method is time‐efficient and produces pathways in good agreement with other state‐of‐the‐art solutions. These paths can serve as first approximations that can be used, analyzed, or improved with more specialized methods. © 2018 Wiley Periodicals, Inc. The study of ligand binding/unbinding pathways has become an important subject for protein engineering and computer‐aided drug design because it allows the prediction of kinetics properties and identification of the important interactions, which hinder/facilitate the ligand entry/exit. The article proposes a new method, ART‐RRT, for generating approximate ligand unbinding pathways in reasonable time. These paths can be used, analyzed, or improved with more specialized methods.